Analisis Karakteristik Tanah Berdasarkan Uji Lapangan Sondir (Cone Penetration Test) & Uji Laboratorium pada PIT North PT Karya Putra Borneo - Yuana Saputra; Revia Oktaviani; Rety Winonazada; Tommy Trides; Albertus Juvensius Pontus (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2026)
This study aims to analyze the characteristics of the soil at PIT North with two highwall and lowwall locations at PT Karya Putra Borneo, Kutai Kartanegara Regency, East Kalimantan Province. The research method was carried out by collecting primary data from the results of field tests using the sondir method with the Cone Penetration Test(CPT) tool and laboratory tests using physical properties, specific gravity, grain size, soil consistency, and consolidation tests, as well as secondary data from the results of literature studies. The parameters analyzed for soil characteristics include the sondir cone resistance (qc) value, grain size fraction distribution, soil plasticity index, and the rate of land subsidence through consolidation. The results showed that at PIT North the highwall area had a qc value of 5.6 Mpa, Fr 0.2%, IP 8.06%, Cc 1, a large rate of land subsidence of 3.3 mm with a settlement period of 4 years. In the lowwall area with a qc value of 10.31 Mpa, Fr 0.16%, IP 6.39%, Cc 0.535, the rate of settlement was 4.4 mm with a settlement period of 3 years. From these results, it is concluded that the soil at the highwall and lowwall locations has different compressibility, seeing the different soil Cc values and the soil plasticity index that affect the compressibility level of the soil and the value of the land settlement rate.